Fluid-inclusion and stable-isotope evidence for fluid infiltration and veining during metamorphism in marbles and metapelites - Frezzotti, M; Dallai, L; Sharp, Z. (European Journal of Mineralogy, 2000)
Syn-metamorphic quartz + carbonate veins within lower-amphibolite-facies marbles and greenschist-facies metapelites of the O'Kane Canyon (northern Victoria Land, Antarctica) are characterised by fluids of different composition: H2O-CO2-CH4 mixtures (34-44 H2O, 50-61 CO2, 3-6 CH4, in mole %) (Type A), or H2O-CO2-N-2 fluids (35-43 H2O 48-54 CO2, 9-11 N-2, in mole %) (Type B). In metapelites, quartz + carbonate veins contain H2O-CO2-CH4 (Type C) fluids, which have a composition 30-68 H2O, 29-64 CO2, 2-6 CH4, in mole %) similar to Type A fluids in marbles. Isochores for both Type A and Type B fluids intersect the estimated peak conditions of 500 degrees C and 3-3.5 kbar, indicating that fluids with different compositions were trapped in the marbles during metamorphic veining. In greenschist-facies metapelites, isochores for Type C fluids cross the metamorphic P-T conditions at 2 kbar and 400 degrees C. Overall isochore distribution indicates early cooling (500-400 degrees C) without significant uplift. For the N-2-bearing Type B fluid inclusions, the delta(13)C value of the CO2 is 2.5 parts per thousand PDB and the delta D of H2O is 0 parts per thousand. The delta(18)O of host vein-quartz is 20.3 parts per thousand, and delta(13)C Of calcite within the host vein and in marble are both -1.5 parts per thousand. Tn contrast, the delta(13)C values of carbonate veins containing Type A H2O-CO2-CH4 fluids are lighter (-5.3 parts per thousand) than in the host marble (-2.9 to -1.5 parts per thousand). Type A fluid inclusions have light delta(13)C CO2 values (0.1 parts per thousand) and delta D H2O values (-84 parts per thousand). Type C inclusions also have light delta(13)C CO2 values (-3.1 parts per thousand), and variable delta D H2O (-30 and 98 parts per thousand). Fluid-inclusion and stable-isotope studies indicate that the analysed quartz-calcite veins formed by local processes in a similar structural context. The veins preserved distinct fluid-inclusion and isotopic compositions, indicating diverse sources of fluids: ...